Software patterns, knowledge maps and domain analysis - Fayad, Mohamed, 1950- (CRC Press, Taylor & Francis Group, 2015)
This book delineates a new creation process and provides an understanding of software pattern languages and true domain analysis, based on the fundamental concepts of software stability. It introduces a very well defined paradigm for creating pattern languages, software patterns, and better software development methodology that leads to highly reusable artifacts and high quality, cost-effective systems. Each chapter of the book concludes with an open research issue, review questions, exercises, and a series of projects.